Comparing Mfd- and UvrD-dependent models of transcription coupled DNA repair in live Escherichia coli using single-molecule tracking - Kaja, E; Vijande, D; Kowalczyk, J; Michalak, M; Gapiński, J; Kobras, C; Rolfe, P; Stracy, M (Elsevier, 2024)
During transcription-coupled DNA repair (TCR) the detection of DNA damage and initiation of nucleotide excision repair (NER) is performed by translocating RNA polymerases (RNAP), which are arrested upon encountering bulky DNA lesions. Two opposing models of the subsequent steps of TCR in bacteria exist. In the first model, stalled RNAPs are removed from the damage site by recruitment of Mfd which dislodges RNAP by pushing it forwards before recruitment of UvrA and UvrB. In the second model, UvrD helicase backtracks RNAP from the lesion site. Recent studies have proposed that both UvrD and UvrA continuously associate with RNAP before damage occurs, which forms the primary damage sensor for NER. To test these two models of TCR in living E. coli, we applied super-resolution microscopy (PALM) combined with single particle tracking to directly measure the mobility and recruitment of Mfd, UvrD, UvrA, and UvrB to DNA during ultraviolet-induced DNA damage. The intracellular mobilities of NER proteins in the absence of DNA damage showed that most UvrA molecules could in principle be complexed with RNAP, however, this was not the case for UvrD. Upon DNA damage, Mfd recruitment to DNA was independent of the presence of UvrA, in agreement with its role upstream of this protein in the TCR pathway. In contrast, UvrD recruitment to DNA was strongly dependent on the presence of UvrA. Inhibiting transcription with rifampicin abolished Mfd DNA-recruitment following DNA damage, whereas significant UvrD, UvrA, and UvrB recruitment remained, consistent with a UvrD and UvrA performing their NER functions independently of transcribing RNAP. Together, although we find that up to ∼8 UvrD-RNAP-UvrA complexes per cell could potentially form in the absence of DNA damage, our live-cell data is not consistent with this complex being the primary DNA damage sensor for NER.